Ranitidine reduced levodopa-induced dyskinesia in a rat model of Parkinson’s disease - Cui, Guiyun (Dove Medical Press, 2013)
BACKGROUND: Chronic administration of levodopa in Parkinson’s disease leads to debilitating involuntary movements, termed levodopa-induced dyskinesia (LID). The pathogenesis of LID is poorly understood. Previous research has shown that histamine H(2) receptors are highly expressed in the input (striatum) and output (globus pallidus, substantia nigra) regions of the basal ganglia, particularly in the GABAergic striatopallidal and striatonigral pathways. Therefore, a histamine H(2) receptor antagonist could be used to reduce LID. In the present work, we investigated whether ranitidine has the potential to diminish LID in rats with dyskinesia and explored the underlying mechanisms involved. METHODS: A rat model of PD was induced by 6-hydroxydopamine. Valid PD rats were then treated with levodopa (25 mg/kg, intraperitoneally) and benserazide (12.5 mg/kg, intraperitoneally) for 21 days to induce a rat model of LID. The acute and chronic effects of administration of ranitidine at different doses (5 mg/kg, 10 mg/kg, and 20 mg/kg) on abnormal involuntary movements, levodopa-induced rotations, and the forelimb adjusting steps test were investigated in LID rats. The chronic effect of ranitidine (10 mg/kg) on the expression of Arc and proenkephalin was also evaluated. RESULTS: Levodopa elicited increased dyskinesia in PD rats. Acute ranitidine treatment had no effect on LID, but chronic ranitidine administration (10 mg/kg, 20 mg/kg) reduced LID in rats with dyskinesia. Importantly, levodopa-induced rotations were not affected by chronic treatment with ranitidine. In addition, chronic ranitidine (10 mg/kg, 20 mg/kg) significantly improved stepping of the lesioned forepaw. Real-time polymerase chain reaction showed that Arc and proenkephalin levels were reduced by chronic ranitidine (10 mg/kg) in dyskinetic rats. CONCLUSION: These data indicate that ranitidine is a good adjunct for reducing LID in rats with dyskinesia. Inhibition of dopamine D1-mediated activation in the medium spiny neurons may account for the antidyskinetic effects of ranitidine in rats with dyskinesia.